Contemporary Issues in Australian Literature : International Perspectives. - Callahan, David (Taylor and Francis, 2014)
The contemporary study of Australian literature ranges widely across issues of general cultural studies, the politics of identity (both ethnic and gendered), and the position of Australia within wider postcolonial contexts. This volume intervenes in the most significant of issues in these areas from a variety of international perspectives.